ANALISIS PROBLEMATIKA STUDY FROM HOME (SFH) PADA MATA PELAJARAN BAHASA INGGRIS DI SMP NEGERI 1 RANAH PESISIR KABUPATEN PESISIR SELATAN MASA PANDEMI COVID-19 - Yani, Titik Hardewi; Saputra, Bobi; A, Taufik Abdul Hasan; Julis, M. (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
The policy issued by the government regarding study from home during the COVID-19 pandemic has created new problems in learning in schools. Students assume that study from home is a holiday activity that they enjoy at home. This kind of learning also causes students to feel bored because every day they face very monotonous activities. This study aims to describe the problems of pedagogy with study from home (SFH) in learning English at SMP Negeri 1 Ranah Pesisir during the COVID-19 pandemic. This study uses a qualitative descriptive method with a case study approach. As the subject of this research, four English teachers teach grades VII, VIII and IX at SMP Negeri 1 Ranah Pesisir. From the data analysis, the researchers obtained the results, namely, 1) the absence of online study from home learning training, so that teachers still lacked experience in improving online SFH learning activities. 3) Limited time with SFH online makes students unable to complete school assignments on time. 4) Lack of parental concern for students because parents are still pretentious with the online SFH learning system, they are not used to being involved in the learning process